Impact Of Ethical Leadership On Organisational Culture With Special Reference To Shipping And Logistics Firms In Chennai (International Journal of Environmental Sciences, 2025)
In the contemporary dynamics of shipping and logistics firms, administrative structure is not merely a blueprint of hierarchy, but it is a vital mechanism that oversees operational efficiency, decision-making suppleness and regulatory compliance. In the face of growing complexity and ethical scrutiny, the main aim of the study is to investigate the impact of ethical leadership on organizational structure, with specific reference to structural clarity, structural adaptability and perceived structural impact. The study has collected the data from 100 middle and lower-level management professionals and employed a quantitative analytical design encompassing descriptive statistics, independent sample t-test, bivariate correlation and linear regression analysis. The findings of the study revealed that 57.9% variance in organizational structure can be significantly and strongly influenced by ethical leadership. It is also found that ethical leaders were found to foster structural clarity, assist adaptive frameworks and aids in bridging hierarchical gap. Moreover, it is revealed that perceptual differences occurred between the middle and lower-level respondents, indicating unpredictable transmission of ethical practices. The study concluded that ethical leadership is not only a moral compass but a structural instrument that ensures alignment, dexterity and accountability. Implications for structural policy, leadership advancement and ethical integration are discussed, offering valuable insights for scholars and practitioners in logistics-intensive industries.